Dural and Multiple Brain Metastases From Basaloid Nasopharyngeal Carcinoma: Case Report and Literature Review - Geng, Xiaotao; Hao, Furong; Han, Guiyan; Zhang, Yaping; Qin, Peiyan (Frontiers in Oncology, 2021)
Background Nasopharyngeal carcinoma is an endemic head and neck cancer in Southern China. The common metastases organs involve bone, lung, and liver. Metastases in the dura and at multiple locations in the brain after a diagnosis of nasopharyngeal carcinoma are extremely rare. Case Presentation We present a case of a 66-year-old man who initially complained of nasal congestion, epistaxis, and hearing impairment. The biopsy of the nasopharynx lesion showed basaloid squamous cell carcinoma. Eight months after conventional therapy, the patient was admitted to our hospital again with the complaint of a headache. A PET/CT scan was performed, revealing multiple metastases. A biopsy of subcutaneous soft tissue from the right upper arm was consistent with the previous biopsy. Palliative chemotherapy was administered. Thereafter, the patient had sudden dysfunction of the right side of the body. MRI demonstrated dural and multiple brain metastases. The therapeutic regimen then consisted of whole-brain radiotherapy, anti-angiogenesis therapy, and immunotherapy. Conclusions This case highlights the diagnosis and treatment of uncommon metastases of nasopharyngeal carcinoma. Clinicians should remain vigilant for metastases during the treatment and follow-up periods.